Budaya Keselamatan Pasien di Layanan Kesehatan: Literature Review terhadap Faktor Penentu dan Strategi Penguatan Budaya Keselamatan Pasien Tahun 2021–2026 - Aniq Alimmuddin; Fajar Adi Wicaksono; F. Heti Widiastuti; Muhidin Muhidin; Sutrisno Sutrisno; Surtinih Surtinih (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Patient safety culture is a fundamental component of delivering high-quality, safe, and patient-centered healthcare services. A strong patient safety culture contributes to reducing adverse events, improving healthcare quality, and establishing a sustainable healthcare system. However, its implementation continues to face several challenges, including underreporting of incidents, limited human resources, excessive workload, and insufficient organizational support. This study aimed to analyze the factors influencing patient safety culture in healthcare settings using a Systematic Literature Review (SLR) approach. The literature search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines and was conducted through PubMed, Scopus, ScienceDirect, Google Scholar, and SpringerLink, covering publications from 2021 to 2025. Article selection was performed using the PICOS framework, resulting in ten eligible studies for analysis. The findings indicate that patient safety culture is influenced by leadership commitment, open communication, effective teamwork, organizational learning, non-punitive incident reporting systems, adequate human resources, and patient engagement. Conversely, a blame culture, heavy workloads, shortages of healthcare professionals, and low incident reporting remain major barriers to implementation. Strengthening patient safety culture therefore requires organizational commitment through leadership development, capacity building for healthcare professionals, fostering a learning culture, and continuous evaluation to improve healthcare quality and minimize patient safety incidents.